Implementasi Pendidikan Iman bagi Santri melalui Program Belajar Bersama Orang Tua di Kuttab Al-Fatih Cimenyan Bandung Level Kuttab Awal Tiga - Muhammad Zulfikar; Aep Saepudin; Fitroh Hayati (UNISBA Press, 2022)
Abstract. The role of parents in children's faith education cannot be completely replaced by the role of the teacher. Therefore, there needs to be good cooperation between parents and teachers in the faith education process that is carried out. The purpose of this study was to determine the planning, implementation, evaluation as well as supporting and inhibiting factors in the implementation of Faith Education for students through the Learning with Parents program at Kuttab Al-Fatih Bandung. This study uses a descriptive method using a qualitative approach to examine the implementation of Faith Education through the Learning with Parents program. Data collection techniques were carried out by means of interviews, observations, and documentation studies. The results showed that: (a). Planning for faith education through the study program with parents consists of preparing a schedule for the BBO program for one academic year by the coordinator of the faith class and making a kuttab activity plan (RKK) made by the faith class teacher. (b). The implementation of faith education through the BBO program is carried out continuously between teachers and parents. Beginning with faith education conducted in the classroom by the faith class teacher, then followed by parents with a faith class assignment guide. (c). The evaluation or assessment used in the BBO program is an attitude assessment that is carried out in stages (d). The supporting factor that dominates the implementation of the program is parents' awareness of the importance of the role of parents in accompanying children when studying at home. While the inhibiting factor is the lack of understanding of parents in the technical implementation and writing feedback on activities that have been carried out at home. Abstrak. Peran orangtua dalam pendidikan iman anak tidak bisa digantikan sepenuhnya oleh peran guru. Oleh karenanya perlu ada kerjasama yang baik antara orangtua dan guru dalam proses pendidikan iman yang dilakukan. Adapun tujuan penelitian ini adalah untuk mengetahui perencanaan, pelaksanaan, evaluasi serta faktor pendukung dan penghambat dalam implementasi Pendidikan Iman bagi santri melalui proram Belajar Bersama Orangtua di Kuttab Al-Fatih Bandung. Penelitian ini menggunakan metode deskriptif dengan menggunakan pendekatan kualitatif untuk meneliti implementasi Pendidikan Iman melalui program Belajar Bersama Orangtua. Teknik pengumpulan data dilakukan dengan cara wawancara, observasi, dan studi dokumentasi. Hasil penelitian menunjukan bahwa: (a). Perencanaan pendidikan iman melalui program berlajar bersama orangtua terdiri dari penyusunan jadwal program BBO untuk satu tahun ajaran oleh koordinator kelas iman dan pembuatan rencana kegiatan kuttab (RKK) yang di buat oleh guru kelas iman. (b). Pelaksanaan pendidikan iman melalui program BBO dilakukan secara berkesinambungan antara guru dengan orangtua. Diawali dengan pendidikan iman yang dilakukan di kelas oleh guru kelas iman, kemudian dilanjutkan oleh orangtua dengan panduan tugas kelas iman. (c). Evaluasi atau penilaian yang digunakan pada program BBO adalah penilaian sikap yang dilakukan secara bertahap (d). Faktor pendukung yang mendominasi pelaksanaan program adalah kesadaran orangtua akan pentingnya peran orantua dalam membersamai anak saat belajar di rumah. Sedangkan faktor penghambatnya adalah kurangnya pemahaman orangtua dalam teknis pelaksanaan dan penulisan feedback atas kegiatan yang telah dilakukan di rumah.